2008
DOI: 10.1002/uog.5363
|View full text |Cite
|
Sign up to set email alerts
|

The value of umbilical artery Doppler velocimetry in the antenatal surveillance of uncomplicated monochorionic twin pregnancies

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
10
1
3
Order By: Relevance
“…Therefore, early diagnosis of chorionicity is vital in twine or multiple pregnancies [6]. So, procedures have been suggested in precise monitoring of fetuses in monochorionic twin pregnancies to prevent morbidity and mortality [4,9,[11][12][13]. It should be noted, however, none of these pathologic entities were present, neither in the study by Ingec et al, nor in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Therefore, early diagnosis of chorionicity is vital in twine or multiple pregnancies [6]. So, procedures have been suggested in precise monitoring of fetuses in monochorionic twin pregnancies to prevent morbidity and mortality [4,9,[11][12][13]. It should be noted, however, none of these pathologic entities were present, neither in the study by Ingec et al, nor in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…The determination of chorionicity is important for predicting the prognosis of pregnancy, because it has been shown that in monochorionic cases, vascular anastomoses or imbalanced placental vascular distribution in the two placentas may lead into the twin insufficiency syndrome. In addition, hemodynamic imbalances may jeopardize the health of both fetuses and cause significant consequences [4,9,10]. A worse prognosis in monochorionic pregnancies is possibly due to the twin to twin transfusion syndrome, growth restriction, and the twin reverse arterial perfusion syndrome in such cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations